STEM Learning in Sustainability Issues to Improve Sustainability Consciousness of Junior High School Students - Rahmania - Firda; Ida Kaniwati; Siti Sriyati (Universitas Sebelas Maret, 2021)
Sustainability Consciousness is the expected result with the existence of ESD that is a complicated construction that can be influenced by various factors. ESD aims to develop students' understanding of sustainability issues and change students' attitudes and behavior regarding environmental, social, and economic sustainability. The purpose of this paper is to determine the improvement of students’ sustainability consciousness after attending STEM learning in sustainability issues. This study used quasi experimental method with one group pretes-posttest design. It was conducted in 28 seventh grades students of junior high school in Surabaya. The instrument was declared as valid based on expert’s judgment and showed Alpha Cronbach score 0,85. Data was collected by pretest and posttest of sustainability consciousness questionnaire. Based on the data analysis, it showed that sustainability issues were effectively integrated into STEM learning to enhance the sustainability consciousness of junior high school students. N-gain average of sustainability consciousness were 0,18 as low category. The findings suggest that required learning strategies that can provide more opportunities for students to learn about sustainability issues and develop pro-sustainability attitudes and behaviors.